2009
DOI: 10.1108/15265940910924481
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of alternative scoring models in private banking

Abstract: Purpose -This paper aims to investigate the efficiency and effectiveness of alternative credit-scoring models for consumer loans in the banking sector. In particular, the focus is upon the financial risks associated with both the efficiency of alternative models in terms of correct classification rates, and their effectiveness in terms of misclassification costs (MCs). Design/methodology/approach -A data set of 630 loan applicants was provided by an Egyptian private bank. A two-thirds training sample was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
(28 reference statements)
4
27
0
1
Order By: Relevance
“…This followed by three ratios namely return on average equity, liquid assets to deposit and short tern funding and equity to total assets with Chi 2 values of 38.758, 24.421 and 21.482, respectively. Our LR 1 Stepwise model results show similar findings as per the LR 1 model. The overall model is statistically significant at the 99% confidence level with R 2 value of 76.64% (R 2 Adj.…”
Section: Logistic Regression Models Results For the First Model (Lr supporting
confidence: 78%
See 1 more Smart Citation
“…This followed by three ratios namely return on average equity, liquid assets to deposit and short tern funding and equity to total assets with Chi 2 values of 38.758, 24.421 and 21.482, respectively. Our LR 1 Stepwise model results show similar findings as per the LR 1 model. The overall model is statistically significant at the 99% confidence level with R 2 value of 76.64% (R 2 Adj.…”
Section: Logistic Regression Models Results For the First Model (Lr supporting
confidence: 78%
“…On theoretical grounds, it might be supposed that logistic regression is a more appropriate statistical tool than linear regression, given that two discrete classes "1" and "0" have been defined (Hand & Henley, 1997;Abdou, 2009). …”
Section: Logistic Regression Logistic Regression (Lr)mentioning
confidence: 99%
“…It is potentially more costly for a bank to misclassify a bad loan as good (Type II) than a good loan as bad (Type I) since in the latter case at worst opportunity cost is involved. These results are consonant with the literature where it has been found that advanced scoring models have lower error rates compared to conventional scoring models (see for example, [1,3,37] ). Our results show the superiority of neural networks in predicting default rate in a stronger and more revealing manner -clearly of considerable economic value in a community where borrowers are all too frequently prone to default.…”
Section: Comparison Of Different Scoring Modelssupporting
confidence: 80%
“…Based on the review carried out, several comments can be outlined: (i) the use of statistical procedures either for determining the optimal method or for comparing the performance of different prediction models appears to be infrequent since more than 68% of papers have not reported any form of hypothesis testing; (ii) the parametric tests have been applied in nearly 18% of papers (especially the t-test with about 15%), but ignoring whether the samples hold the normality and homoscedasticity assumptions or not; (iii) approximately 13% of papers have included a non-parametric test in the experimental protocol, being the McNemar's (5.67%) and Wilcoxon's signed-ranks (3.55%) tests the two most common techniques; (iv) only three papers (Canbas et al 2005;Abdou et al 2008;Abdou 2009a) have studied the statistical difference of variances through Bartlett's, Levene's or Cochran's C tests; and (v) the post hoc tests for comparisons with a control algorithm have seldom been applied, with only seven works using the Tukey's method (Pendharkar 2005), the Nemenyi's test (García et al 2012;Marqués et al 2013;Brown and Mues 2012), the Holm's test (Hu and Chen 2011) or the Bonferroni-Dunn's procedure (Marqués et al 2012a,b).…”
Section: Statistical Tests Of Significancementioning
confidence: 99%